Development of 3D VR models and animations - Wu, Hao (Nanyang Technological University, 2022)
The use virtual reality is widely used in market as of today, it is a computer modelling technique that simulates the real world environment. The virtual reality environment is able to simulate human senses such as sight, touch and hearing. In order to generate a three dimensional environment effect, stereoscopic pair images have to be formed on the display for the view of both the left and right eyes of a human at different angles.